Indonesia Economic Quarterly, September 2010 : Looking Forward - World Bank (World Bank, Washington, DC, 2018)
The Indonesian economic quarterly reports on and synthesizes the past three months' key developments in Indonesia's economy. It places them in a longer-term and global context, and assesses the implications of these developments and other changes in policy for the outlook for Indonesia's economic and social welfare. Its coverage ranges from the macro-economy to financial markets to indicators of human welfare and development. It is intended for a wide audience, including policy makers, business leaders, financial market participants, and the community of analysts and professionals engaged in Indonesia's evolving economy. Indonesia's economy continues to record robust growth, in contrast with the volatility and uncertainty characterizing major economies globally. The robustness of growth has allowed the policy focus to shift from near-term uncertainty towards achieving the investments and reform required to achieve sustained and strong growth over the longer-term. Meeting the Government's target of over 7 percent growth by 2014 requires strong rises in investment, particularly in infrastructure, and in skills and productivity. Quarterly output accelerated in Q2, resulting in year-on-year growth of 6.2 percent, the highest since the onset of the global economic crisis two years earlier. Domestic demand, particularly private consumption, underpins the growth performance and has been associated with rising imports, particularly for investment and intermediate goods. Slow disbursement of government expenditures continue to act as a drag on growth, but less so than in Q1. Indonesia's trading partners also recorded stronger growth than expected, although the overall contribution of net external demand to growth was negative in Q2. Correspondingly, domestic-oriented sectors outperformed externally-oriented sectors.